Problematika Fleksibilitas Outsourcing (Alih Daya) Pasca-Undang-Undang Nomor 11 Tahun 2020 tentang Cipta Kerja Klaster Ketenagakerjaan - Sela Nopela Milinum (Jurnal Hukum Lex Generalis, 2022)
The abolition of Articles 64, 65, and the revision of Article 66 of the Labor Law regarding the limitation of the outsourced work in the Job Creation Law have sparked conflict among workers. The reason is because the Outsourcing regulation in the Job Creation Law is considered to exploit and marginalize the humanitarian side of workers. The purpose of the research is to examine the problems of Outsourcing regulation after the Job Creation Law that will provide flexibility for employers to use outsourced workers that can trigger modern slavery practices, decreased certainty of permanent employment, and vulnerability of workers' rights.